A rare case report of appendix and cecum in the sac of left inguinal hernia (left Amyand's hernia) - Ghafouri, Ali (Tehran University of Medical Sciences, 2012)
This case is a rare aspect of left inguinal hernia. The patient was a 60-years old man with left scrotal mass since childhood. In the operating room, the hernia sac was opened which included cecum and appendix that is called left Amyand‘s hernia. The patient underwent herniorrhaphy with Lichtenstein repair.